Jadoowallahs, Jugglers and Jinns: A Magical History of India - John Zubrzycki (Picador India, 2018)
India's association with magic goes back thousands of years - from the seals of Mohenjodaro that depicted sorcerers and yogis, to the jugglers, mountebanks and acrobats that dazzled audiences at the courts of Hindu maharajas and Mughal emperors. Tales were told of ropes being thrown up in the air, strong enough for a boy to climb and disappear; of fakirs being buried alive for months and brought back to life; and of sanperas charming deadly cobras with their flutes. In the early nineteenth centur y, touring Indian magicians mesmerized audiences abroad, prompting generations of Western illusionists to emulate their Eastern peers. Jadoowallahs, Jugglers and Jinns: A Magical History of India tells us how Indian magic descended from the domain of the gods to become part of daily ritual and popular entertainment, and its transformation from the street to the stage culminating with the rise of the great P. C. Sorcar Sr. Drawing on ancient religious texts, colonial records, newspaper reports, journals and the memoirs, diaries and testimonies of Western and Indian magicians, John Zubrzycki offers us a vibrant narrative on Indian magic from ancient times to the present day. John Zubrzycki is a Sydney - based author. He has a degree in South Asian history a nd Hindi from the Australian National University and has worked in India as a foreign correspondent, diplomat and tour guide. His first book, The Last Nizam: An Indian Prince in the Australian Outback , is a bestseller in India.